Предмет: Алгебра,
автор: sonapisnaa
4. Спростити вираз: a)a² + (3a² – a + 7) + (-a² + 9a – 4); б) (x + 2)(x + 4) - (x + 1)(x + 5). срочно (даю 25
Ответы
Автор ответа:
2
Объяснение:
а) а²+(3а²-а+7)+(-а+9а-4)= а²+3а²-а+7-а+9а-4=4а²+7а+3
б) (х+2)(х+4)-(х+1)(х+5)=х+2×х+4-х-1=2х+8-х-1=х+7
sonapisnaa:
спасибо
Похожие вопросы
Предмет: Биология,
автор: ehdhshwhhw
Предмет: Русский язык,
автор: akbota1304
Предмет: Английский язык,
автор: alisermedetov49
Предмет: Английский язык,
автор: osjka2
Предмет: Литература,
автор: elichev3